2013
DOI: 10.1177/1062860613503364
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Handoff Practices in Emergency Medicine

Abstract: This study aimed to assess practices in emergency department (ED) handoffs as perceived by emergency medicine (EM) residency program directors and other senior-level faculty and to determine if there are deficits in resident handoff training. This cross-sectional survey study was guided by the Kern model for medical curriculum development. A 12-member Council of Emergency Medicine Residency Directors (CORD) Transitions in Care task force of EM physicians performed these steps and constructed a survey. The surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This is consistent with the existing literature, which showed that less than half of EM programs had a standardized handoff practice in 2013 12. A standardized handoff practice has been introduced to several inter-unit handoff processes, namely using mnemonics and checklists 14,31.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the existing literature, which showed that less than half of EM programs had a standardized handoff practice in 2013 12. A standardized handoff practice has been introduced to several inter-unit handoff processes, namely using mnemonics and checklists 14,31.…”
Section: Discussionsupporting
confidence: 90%
“…www.surveymonkey.com) and distributed to all members through the CORD listserv. The validity of using the CORD listserv as sample population has been described elsewhere 7,11,12. The responses were collected, and duplicated responses were removed and compiled for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a literature review of previous surveys done on ED handoffs and identified one study as a model 12. We based the first half of the survey questions on this study.…”
Section: Methodsmentioning
confidence: 99%
“…This task force included EM residency program directors (PDs), academic chairpersons, and other EM faculty. The survey content underwent a thorough development process . The expertise of those involved in the development of the survey contributed to the validity of its content .…”
Section: Methodsmentioning
confidence: 99%
“…The objectives of the survey study were to 1) assess the scope of current handoff practices amongst EM residents through the experience of their residency program director and/or other senior faculty and 2) to assess current educational and evaluation practices related to handoffs. The current survey is a follow‐up survey to our initial 2011 study of U.S. EM residencies . Given the ever‐increasing emphasis on transitions of care in medicine, we sought to determine if interval changes in resident transition of care education, assessment, and proficiency have occurred.…”
mentioning
confidence: 99%